Metropolitan Finance Reconsidered: Budget Functions and Multi-Level Governments - Tiebout, Charles M.; Houston, David B. (The Review of Economics and Statistics, 1962)
HE current chaos in metropolitan fiT nance stems from two different sets of problems. The first, which we label traditional, are exemplified by such expressions as: ever-increasing demands for service, inadequate tax base, archaic tax structure, lack of planning, and other familiar expressions. Without doubting that these problems are acute and in need of attention, we wish to consider an overlooked second set of problems. The second set of problems arises when the budget functions of governments are placed within the context of the newly developed theory of public finance.' Here, governments are seen as performing certain overall budget functions provision of goods and services, income redistribution, and economic stabilization. However, except for the provision of one class of goods and services, namely, social goods, little attention has been focused on the budget problems involved in applying the newer theory to lower levels of government and the attendant problems of fiscal federalism which arise. We will argue that much of the chaos in metropolitan finance arises from a misunderstanding of the budget functions to be performed. The heart of the problem, it will be shown, lies in the vertical relations between governmental units. Under fiscal federalism the failure to solve problems of vertical relations, in turn, gives rise to certain horizontal conflicts between governmental units. While our discussion applies to lower-level governments in general, we focus attention on metropolitan areas where the problems are more vividly illustrated. The analysis will be structured in terms of the various budget functions which governments perform. The provision of social goods will be considered briefly. Next, we look into certain interferences with consumer sovereignty (merit goods) which governments undertake. Finally, issues involved when governments redistribute income will be considered.2 For each function we postulate a set of vertical rules ordering the relations between governments. This ordering will enable us to highlight the issues involved.